Здоровий спосіб життя та дозвілля сучасної студентської молоді Закарпатського угорського інституту імені Ференца Ракоці ІІ - Чегіль Аніко; Csehil Anikó; Aniko Chehil (Видавництво «Код», 2023)
Резюме. Дані про охорону здоров’я підтверджують скорочення тривалості життя населення та існування поганого стану здоров’я. Основними причинами смертності є хронічні захворювання. За оцінками ВООЗ, відсутність фізичної активності є причиною 3,2 мільйона смертей, що робить його четвертою основною причиною смерті у світі.

Abstract. Public health data support the shortening of the population’s life expectancy and the existence of poor health conditions. The leading causes of death behind the death rate are chronic diseases. Based on WHO estimates, physical inactivity is responsible for 3.2 million deaths, making it the fourth leading cause of death worldwide. Based on EUROSTAT data, the causes of death in the EU are diseases affecting the circulatory and respiratory system, as well as cancer and tumors, in the prevention of which regular sports can play a decisive role. In addition to the indicator of economic development, income inequality, unemployment, education, development of health care, and health-conscious behavior have a multiple impact on life expectancy. A balanced, healthy person is productive, and as a result of this harmonious existence, the joy of life, well-being, satisfaction, work ethic, creativity, fitness, physical, psychological, social adaptability, etc. are usually the result. inherent. During the examination of health-preserving behavior with the help of a questionnaire, we got an idea of the lifestyle of the students of education and, in connection with this, their state of health. According to the data of physical indicators provided by them, the body structure of the students corresponds to the average indicators. According to the subjective statement, positive results of self-assessment of the state of health were obtained: 77 percent of the respondents recognized their health as good or even excellent, but the vast majority of them visited a doctor during the last year for the purpose of eliminating minor problems, illnesses and rehabilitation (almost 60 percent), which cause concern in the near future.
Healthy way of life and leisure of modern student youth of the Transcarpathian Hungarian Institute named after Ferenc Rakoczi II
https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-4
Keywords: спосіб життя; охорона здоров’я; звички; вільний час; студентська молодь